The Role of SIM-RIwinK in the Form of Smart Village Transformation in the Implementation of Administrative Management in Wringinsongo Village Malang Regency - Suljatmiko (Faculty of Social and Political Science, 2025)
This study investigated the implementation of the smart village program in Wringinsongo Village, East Java, with a focus on the success of the SIM-RIwinK application in transforming administrative correspondence between central government authorities, village governments, and residents from conventional methods. With a descriptive qualitative approach, this study explores the experiences of heads of families, online service providers, and villagers through in-depth interviews, observations, and documentation. Data analysis was carried out using the Miles and Huberman Qualitative Data Analysis Model, an interactive framework that involves three processes that occur simultaneously: data reduction, i.e. selection, focusing, and simplification of data related to the implementation and impact of SIM-RIwinK, data presentation, including organizing information through matrix and narrative to identify patterns of administrative governance, and verification, namely interpreting the data that has been presented and validating the findings obtained through triangulation and reflection. The findings of the study show the important role of the SIM-RIwinK application in the successful transition to smart village governance by streamlining the administrative process. This research offers valuable insights for future scientific research and provides a model of success that can be replicated by village governments in Malang Regency who want to improve their administrative services through technological innovation